Profil Self Efficacy dalam Menyelesaikan Soal Matematika Materi Sistem Persamaan Linier Dua Variabel Siswa Kelas VIII SMP Negeri 4 Jember - Setiawan, Toto Bara; Hobri, Hobri; Arsita, Putri Ayu (Kadikma, 2017)
Abstract: The aim of this research is to describe self efficacy profile to solve mathematics problems material system of linear equations of two variables in eighth grade students of SMP Negeri 4 Jember. This research is a qualitative research and implemented in academic year 2016/2017. Documentary is used in this research as data collection because the researcher collecting data from UTS of student mathematics, test method, and interview method, while the instrument that being used is a mathematics problem test of system of linear equations of two variables (SPLDV) and interview guidelines. Subjects of this research are all eight grade students of SMP Negeri 4 Jember, consisting of 15 male students and 20 female students. The results showed that students' self efficacy is varied. Of the 35 students who are the subject of research, 28 students of whom have a high self-efficacy, while seven other students have a low self-efficacy. In viewing the students’ self efficacy, the researcher uses self efficacy dimension that is the dimension of level, generality, and strength. In dimension of level, almost all of students indicate an attempt to solve problem with different difficulty levels, although there are still 2 students who do not try to do certain problems but in other problems they are still trying to solve (do). In dimension of generality, the mastery of the students in fields be found in the questions also varies. However, most of them show wide field mastery because they are able to solve the given problem. In the strength dimension, the level of students' confidence in solving the problems and their expectations with the correct answers are also varied. Confidence and hope that is within the students mostly adapted to the attemp they do. Students are said to have a high self efficacy when showing the effort to solve problems with different levels of difficulty (level), mastery of the wide field of (generality), and strong confidence and hope that exist in students according to the efforts they do (strength). Keywords: self efficacy, mathematical problem solving, system of linear equation of two variables